The Impact of Abusive Supervision on Organizational Identification: A Moderated Meditation Analysis of Hotel Employees in Antalya - Cengiz, Mustafa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This study investigated the effect of abusive supervision on employee organizational identification by analyzing the mediating effect of psychological contract violation. In addition, it explored the moderating role of favoritism in the direct association of abusive supervision and the organizational identification and the indirect effect through psychological contract violation. A total of 488 seasonal, immigrant and part time employees from family-run hotel organizations were surveyed during the data collection process. By utilizing Hayes’s macro, we found that abusive supervision and psychological contract violation had a significant negative effect on organizational identification. In addition, the results showed that psychological contract violation mediated the effect of abusive supervision on organizational identification and favoritism moderated the effect of abusive supervision on psychological contract violation. The findings highlight the detrimental effects of favoritism and abusive supervision on employee outcomes in the hospitality industry. Keywords: Abusive supervision, favoritism, psychological contract violation, identification, family firms

ÖZ: Bu çalışmanın amacı, istismarcı yönetimin, çalışanların örgütsel özdeşleşme algısı üzerindeki etkisini araştırmaktır. Buna ek olarak, psikolojik sözleşme ihlalinin istismarcı yönetim ve örgütsel özdeşleşme arasındaki aracılık rolü, çalışmada irdelenmiştir. Çalışmada ayrıca, istismarcı denetim ve örgütsel özdeşleşme arasındaki doğrudan ilişkide kayırmacılığın moderatör rolünü ve psikolojik sözleşme ihlali yoluyla dolaylı etkisi araştırılmıştır. Veri toplama sürecinde, aile tarafından işletilen otel işletmelerinde; toplam 488 mevsimlik, göçmen ve yarı zamanlı çalışana anket dağıtılmıştır. Hayes'in Process Macro istatistiki yaklaşımı ele alınarak, istismarcı yönetim ve psikolojik sözleşme ihlalinin, örgütsel özdeşleşme üzerinde önemli bir olumsuz etkisi olduğu bulunmuştur. Ayrıca, elde edilen bulgular, psikolojik sözleşme ihlalinin, istismarcı yönetimin örgütsel özdeşleşme üzerindeki etkisine aracılık ettiğini ve istismarcı yönetimin psikolojik sözleşme ihlali üzerindeki etkisini kayırmacılığa sebep olduğunu göstermiştir. Anahtar Kelimeler: İstismarcı yönetim, kayırmacılık, psikolojik sözleşme ihlali, örgütsel özdeşleşme, aile işletmeleri
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2022. Supervisor: Prof. Dr. Hüseyin Araslı
Keywords: Tourism; Organizational behavior--Psychology, Industrial--Organizational effectiveness; Tourism--Hotel Employees--Organisational Identification; Work Attitudes--Job Satisfaction; Human Resources Management; Abusive supervision; favoritism; psychological contract violation; identification; family firms